JENIS SERANGGA YANG DITEMUKAN DI PERTANAMAN COKELAT DAN KONTRIBUSINYA PADA MATERI BIOLOGI SMA/MA (Universitas PGRI Sumatera Barat, 2019)
This study aims to determine types of insect in cocoa plantations and thecontribution for the tenth-grade student of General/Religion Senior HighSchool Insect topics. This research is research-based development. Theresearch in the field used descriptive survey method and for the developmentresearch used the 4D model which consisted of four stages namely define,design, develop and disseminate. This research only reached the developingstage (validation test). Data were analyzed by using percentage techniquesand descriptive processed. Based on the research finding, that there wereeleven kinds of the Insect in cocoa plantations likes Aulachopora similis,Aulachopora lewisii, Tribolium confusum, Diogmites sp., Batrocera sp.,Leptocorisa acuta, Pseudococcus citri, Bothorogonia ferruginea,Dolichoderus thoracicus, Oecophylla smaragdina dan Lamprosemaoctasema. From the results of this research, Insecta topics in the form of abooklet has been developed which is very valid.